2023
DOI: 10.1371/journal.ppat.1010986
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic interference blocks influenza A virus propagation by impairing viral polymerase-driven synthesis of genomic vRNA

Abstract: Influenza A virus (IAV), like any other virus, provokes considerable modifications of its host cell’s metabolism. This includes a substantial increase in the uptake as well as the metabolization of glucose. Although it is known for quite some time that suppression of glucose metabolism restricts virus replication, the exact molecular impact on the viral life cycle remained enigmatic so far. Using 2-deoxy-d-glucose (2-DG) we examined how well inhibition of glycolysis is tolerated by host cells and which step of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Importantly, we revealed that CD36-OE reversed suppressive effects of D-mannose on PA-induced mEV release (Figure 6L and M), indicating that CD36 was the key to mediating D-mannose effects. To further investigate how D-mannose may regulate CD36 expression in macrophages, we applied chemical inhibitors of MPI and protein N-glycosylation to respectively block each of the two metabolic cascades of D-mannose 16,26,27 . We have also tested metabolites of D- mannose along the cascades, mannose-6-phosphate (M6P), mannose-1-phosphate (M1P) and fructose-6-phosphate (F6P), by treating PA-conditioned macrophages instead of D- mannose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, we revealed that CD36-OE reversed suppressive effects of D-mannose on PA-induced mEV release (Figure 6L and M), indicating that CD36 was the key to mediating D-mannose effects. To further investigate how D-mannose may regulate CD36 expression in macrophages, we applied chemical inhibitors of MPI and protein N-glycosylation to respectively block each of the two metabolic cascades of D-mannose 16,26,27 . We have also tested metabolites of D- mannose along the cascades, mannose-6-phosphate (M6P), mannose-1-phosphate (M1P) and fructose-6-phosphate (F6P), by treating PA-conditioned macrophages instead of D- mannose.…”
Section: Resultsmentioning
confidence: 99%
“…After internalization, D-mannose is phosphorylated by hexokinase to produce M6P, which undergo two major metabolic fates: a minor fraction (∼5%) is isomerized to M1P by PMM2 to be used in glycosylation pathways; the large majority (∼95%) is converted to F6P by MPI to be catabolized into glycolysis 16 . Therefore, to investigate the D-mannose metabolic effect, Tunicamycin (MedChemExpress, China) was used to block protein N-glycosylation 26 at 100 ng/mL for 48 h, and MLS0315771 (MedChemExpress, China) was applied to suppress MPI 27 at 5 mM for 48 h, the dose and duration were selected based on our preliminary dose-effect tests on macrophage viability (data not shown). Furthermore, to test the effects of D-mannose metabolites, M6P (Aladdin, China) was used at 25 mM (equal to the D-mannose concentration) for 48 h, M1P (Aladdin, China) was used at 1.25 mM (5% of the D-mannose dose) for 48 h, and F6P (Yingxinbio, China) was used at 23.75 mM (95% of the D-mannose dose) for 48 h. PA (Kunchuang Biotechnology, China) was added at 500 μM for 24 h based on our preliminary dose-effect tests on macrophage viability (data not shown) and previous research on regulating RAW 264.7 cells and EV release 28,29 .…”
Section: Methodsmentioning
confidence: 99%